ASSESSMENT OF MICRONUTRIENT (Fe, Cu AND Mn) CONCENTRATIONS IN SOIL FROM CACAO PLANTATION COASTAL AREAS, EAST LUWU REGENCY - Ina Oktaviani Simanjuntak; Alfian Noor; Nursiah La Nafie; Asma Assa (Hasanuddin University, 2019)
Micronutrients Fe, Cu and Mn, despite being required in only small amount, have an important role in cacao plant metabolism. This study aims to assess of micronutrient (Fe, Cu and Mn) concentrations in soil from cacao plantation coastal areas, East Luwu Regency. Availability of micronutrient (Fe, Cu and Mn) were analyzed by dry ash method and measured with Inductively Coupled Plasma (ICP). The results showed that Iron (Fe) was represented in large quantities (788.80 mg/100 g). Copper (Cu) and Manganase (Mn) were represented in small quantities 21.65, and 4.34 mg/100 g, respectively.